How do Argentine businessmen and sea workers think about incidental catch and discarding of fish? - Schulze, María Soledad (2024)
[Introduction]: Bycatch and discards are a socio-environmental concern that threatens the sustainability of marine life and fishing grounds. Approaches to this problem have focused on biological and/or ecological aspects. We considered it necessary to explore the problem from the social dimension and for this purpose we explored social representations.  [Objective]: The aim of this study is to explore the social representations of bycatch and discards in a group of businessmen and workers in the capture stage of the Argentine industrial fishing activity. We ask how they evaluate bycatch and fishing discards, what are their causes and if they observe possible solutions. [Methodology]: Within the framework of a project of the Federal Fishing Council, we conducted focus groups with businessmen, business chambers, SOMU workers and captains of the industrial fishing activity. [Results]: The results of the focus groups conducted in 2021 reveal three main causes of this problem. First, the lack of reliable data on actual discard levels raises concerns about sustainability and overfishing. Second, the low utilization of selectivity devices is attributed to their operational inefficiency and possible labour barriers. Finally, economic and organizational pressures, such as company profitability and workers' salaries, justify the discard of non-target species, exacerbating the problem. [Conclusions]: The work contributes to an understanding of the main reasons for bycatch and discards, which is essential to advance solutions. We understand that solutions are not simple and involve a sincere debate among stakeholders.